Ribonucleotide Reductase Expression in Cervical Cancer: A Radiation Therapy Oncology Group Translational Science Analysis. Issue 4 (1st May 2013) - Kunos, Charles A.; Winter, Kathryn; Dicker, Adam P.; Small, William; Abdul-Karim, Fadi W.; Dawson, Dawn; Jhingran, Anuja; Valicenti, Richard; Weidhaas, Joanne B.; Gaffney, David K.
Abstract : Objective: To evaluate pretherapy ribonucleotide reductase (RNR) expression and its effect on radiochemotherapeutic outcome in women with cervical cancer. Methods/Materials: Pretherapy RNR M1, M2, and M2b immunohistochemistry was done on cervical cancer specimens retrieved from women treated on Radiation Therapy Oncology Group (RTOG) 0116 and 0128 clinical trials. Enrollees of RTOG 0116 (node-positive stages IA–IVA) received weekly cisplatin (40 mg/m 2 ) with amifostine (500 mg) and extended-field radiation then brachytherapy (85 Gy). Enrollees of RTOG 0128 (node-positive or bulky ≥5 cm, stages IB-IIA or stages IIB-IVA) received cisplatin (75 mg/m 2 ) on days 1, 23, and 43 and 5-FU (1 g/m 2 for 4 days) during pelvic radiation then brachytherapy (85 Gy), plus celecoxib (400 mg twice daily, day 1 through 1 year). Disease-free survival (DFS) was estimated univariately by the Kaplan-Meier method. Cox proportional hazards models evaluated the impact of RNR immunoreactivity on DFS. Results: Fifty-one tissue samples were analyzed: 13 from RTOG 0116 and 38 from RTOG 0128. M1, M2, and M2b overexpression (3+) frequencies were 2%, 80%, and 47%, respectively. Low-level (0–1+, n = 44/51) expression of the regulatory subunit M1 did not associate with DFS ( P = 0.38). High (3+) M2 expression occurred in most (n = 41/51) but without impact alone on DFS (hazard ratio, 0.54; 95% confidence interval, 0.2–1.4; P = 0.20). After adjusting for M2b status, pelvic node–positive women had increased hazard for relapse or death (hazard ratio, 5.5; 95% confidence interval, 2.2–13.8; P = 0.0003). Conclusions: These results suggest that RNR subunit expression may discriminate cervical cancer phenotype and radiochemotherapy outcome. Future RNR biomarker studies are warranted.